Determinants of Attitude Towards Depression and Suicidal Ideation Among Postpartum Women in Southern Nigeria (Central Asian Journal of Medical Sciences, 2024)
Objective: The objective of this study was to assess the determinants of attitude towards depression and suicidal ideation among postpartum women in Southern Nigeria. Methods: An analytical cross-sectional study using interviewer-administered structured questionnaires involved 480 mothers attending the postnatal clinics at the University of Benin Teaching Hospital, Benin City, Edo State. Data collected was analyzed using SPSS version 25. 0 statistical software with statistical significance set at P < 0.050. Results: The mean age of respondents studied was 31.3 ± 5.7 years. Four hundred and forty-four (92.5%) and 36 (7.5%) respondents had negative and positive attitudes towards depression and suicidal ideation, respectively. Age (OR = 0.809; 95%CI = 0.725 – 0.905; P